2000
DOI: 10.1086/317213
|View full text |Cite
|
Sign up to set email alerts
|

An Optical Time Delay Estimate for the Double Gravitational Lens System B1600+434

Abstract: We present optical I-band light curves of the gravitationally lensed double QSO B1600]434 from observations obtained at the Nordic Optical Telescope (NOT) between 1998 April and 1999 November. The photometry has been performed by simultaneous deconvolution of all the data frames, involving a numerical lens galaxy model. Four methods have been applied to determine the time delay between the two QSO components, giving a mean estimate of *t \ 51^4 days (95% conÐdence level). This is the fourth optical time delay … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
113
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 23 publications
4
113
0
Order By: Relevance
“…Figure 22 shows the result of the simultaneous modeling of 5 systems with time delays obtained at the NOT. These are RX J0911+055 (Hjorth et al 2002), SBS B1520+530, (Burud et al 2002b), B1600+434 (Burud et al 2000) and J0951+263 (Jakobsson et al 2005) and the time delay of SDSS J1206+4332 reported in this paper. On the histogram the results of our simultaneous modeling of the 5 QSOs are presented.…”
Section: Simultanous Modelingsupporting
confidence: 54%
See 1 more Smart Citation
“…Figure 22 shows the result of the simultaneous modeling of 5 systems with time delays obtained at the NOT. These are RX J0911+055 (Hjorth et al 2002), SBS B1520+530, (Burud et al 2002b), B1600+434 (Burud et al 2000) and J0951+263 (Jakobsson et al 2005) and the time delay of SDSS J1206+4332 reported in this paper. On the histogram the results of our simultaneous modeling of the 5 QSOs are presented.…”
Section: Simultanous Modelingsupporting
confidence: 54%
“…The algorithm has been implemented in various analysis of quasars (Burud et al 2000(Burud et al , 2002aHjorth et al 2002;Jakobsson et al 2005;Vuissoz et al 2007;Eigenbrod et al 2006a).…”
Section: Photometrymentioning
confidence: 99%
“…Applied to the galaxy 87GB[BWE91] 1600 +4325 ABS01 by Burud et al (2000), to obtain a distance of 1,920 Mpc.…”
Section: Gravitational Lenses (G Lens)mentioning
confidence: 99%
“…The background quasar is variable in both optical and radio bands, thus allowing time delay measurements from monitoring observations (Jaunsen & Hjorth 1997;. A time delay of 47 +12 −9 days has been determined from the radio monitoring , and a delay of 51 ± 4 days from the optical observations (Burud et al 2000).…”
Section: Introductionmentioning
confidence: 99%